(untitled) (Interdisciplinary Studies Journal, 2024)
This article is part of a doctoral thesis in progress and its main objective is to analyze the importance of memory and institutional identity in forming a sense of belonging among students at an educational institution. The theme is approached through a narrative that interweaves concepts, experiences and various voices, contributing to a contextualized and interdisciplinary debate. Thus, the research adopts a qualitative approach, due to the subjectivity of the phenomena examined, focusing on an extensive literature review, since data analysis has not yet been carried out. The study highlights the challenges presented by the teaching-learning process, considering the challenges of identities in liquid modernity, driven by the process of globalization and technological advances. The approach to the theme of memory, identity and belonging in its various dimensions aims to contribute to a deeper understanding of these challenging aspects, seeking more effective measures to deal with diversity in the educational context. By exploring this theme, the aim is not only to enrich academic knowledge, but also to contribute to the construction of more equitable and inclusive public policies in educational institutions.